Serum IFI16 and anti‐IFI16 antibodies in psoriatic arthritis. (15th October 2019) - De Andrea, M.; De Santis, M.; Caneparo, V.; Generali, E.; Sirotti, S.; Isailovic, N.; Guidelli, G. M.; Ceribelli, A.; Fabbroni, M.; Simpatico, A.; Cantarini, L.; Gisondi, P.; et al.
Summary: Nuclear interferon‐inducible protein 16 (IFI16) and anti‐IFI16 antibodies have been detected in subjects with several rheumatic diseases, often correlating with disease severity, and in this study we investigated their prevalence and clinical associations in psoriatic arthritis (PsA) compared to psoriasis (Pso). We tested sera and synovial fluids of patients with PsA for IFI16 protein levels by capture enzyme‐linked immunosorbent assay (ELISA) and for anti‐IFI16 immunoglobulin (Ig)G and IgA by ELISA, protein radio‐immunoprecipitation and immunoprecipitation‐Western blot of IgG. Sera from patients with Pso and healthy subjects were used as controls, and in a subgroup of patients with PsA we also studied sera after treatment with etanercept. IFI16 was detectable in the sera of 66% of patients with Pso, 46% with PsA and 19% of controls. Among PsA cases, 51% of IFI16‐positive cases had elevated levels of C‐reactive protein (CRP) compared to 31% of patients with undetectable IFI16. Anti‐IFI16 of both IgG and IgA isoforms were detected with significantly higher frequency in PsA and Pso compared to healthy controls, with higher IgG titres in patients with elevated C‐reactive protein (CRP) ( P = 0·015). Immunoprecipitation confirmed the presence of anti‐IFI16 IgG antibodies and these preferentially recognized epitopes outside the N‐terminus of the protein. Lastly, IFI16 was detected in one of seven and anti‐IFI16 in three of seven synovial fluids from patients with PsA. Therefore, IFI16 and anti‐IFI16 are detectable in serum and synovial fluid of PsA patients, especially in cases of elevated CRP. Abstract : IFI16 and anti‐IFI16 are associated with higher disease activity and treatment response in psoriatic arthritis patients.